2018
DOI: 10.1002/bse.2260
|View full text |Cite
|
Sign up to set email alerts
|

Payments for ecosystem services and corporate social responsibility: Perspectives on sustainable production, stakeholder relations, and philanthropy in Thailand

Abstract: Payments for ecosystem services (PES) are environmental management tools that enable corporations to simultaneously enhance their environmental performance and fund sustainable development in rural areas. PES is primarily promoted as part of a sustainable production strategy for conserving natural resources, offsetting carbon emissions, and green supply chain management. Nevertheless, PES uptake by the private sector remains low, and few studies have analysed whether corporate‐financed PES schemes conform to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 71 publications
0
26
0
Order By: Relevance
“…Aside from perceiving conservation issues as relevant, prospective benefits are decisive for a favourable attitude, especially image gains, employee retention and motivation, as well as the protection of natural resource inputs. This is an important result of our study, given that some previous studies found that companies typically consider biodiversity and ecosystem services commitments as philanthropy with only a few own benefits to be gained in return (Koellner et al, 2010; Krause & Matzdorf, 2019; Smith et al, 2018; Thompson, 2018b). Similar to our result, Hassan et al (2020) argued that disclosures about company impacts on biodiversity and threatened species stems from self‐interest instead of a selfless desire to preserve the environment.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Aside from perceiving conservation issues as relevant, prospective benefits are decisive for a favourable attitude, especially image gains, employee retention and motivation, as well as the protection of natural resource inputs. This is an important result of our study, given that some previous studies found that companies typically consider biodiversity and ecosystem services commitments as philanthropy with only a few own benefits to be gained in return (Koellner et al, 2010; Krause & Matzdorf, 2019; Smith et al, 2018; Thompson, 2018b). Similar to our result, Hassan et al (2020) argued that disclosures about company impacts on biodiversity and threatened species stems from self‐interest instead of a selfless desire to preserve the environment.…”
Section: Discussionmentioning
confidence: 74%
“…Generally, the higher the benefit expectations for the company, the more likely are activities for nature conservation. Companies typically expect communication and image gains from a voluntary nature conservation engagement, whereas other benefit expectations, for example, business risk reduction, cost reduction or innovation, are not commonly perceived (Krause & Matzdorf, 2019; Smith et al, 2018; Thompson, 2018b). Benefit expectations seemingly differ, though, depending on the specific type of engagement: Gattás, De Campos, Barakat, and Orsato (2019) investigated reasons for voluntary ecosystem services valuation and found that access to knowledge and risk mitigation were strong motivations, whereas reputational gains and innovation were weak motivations.…”
Section: Theoretical Model and Hypothesesmentioning
confidence: 99%
“…Private commercial landowners are most similar to the rural land managers that existing PES schemes usually target (Grima, Singh, Smetschka, & Ringhofer, ); for example, farmers in the Vittel™ PES scheme in France (Perrot‐Maître, ) and Sloping Land Conversion Program in China (Pan, Xu, Yang, & Yu, ). Private non‐commercial landowners also act as providers in rural PES schemes, such as property owners in Uganda that are paid not to cut trees for charcoal (Jayachandran et al, ), or communities with de facto land tenure in Thailand that construct check‐dams to enhance water retention in catchments (Thompson, ). Few rural PES schemes involve public providers (Grima et al, ), although there are rare examples of State‐led provision in Bolivia (Pereira, ) and Madagascar (Brimont et al, ).…”
Section: Typology Of Providers Of Urban Ecosystem Servicesmentioning
confidence: 99%
“…In addition, green production can be considered as a leading strategy for enterprises to cultivate and improve their green dynamic capability (Augusto de Oliveira et al, 2019; Thompson, 2019). In this case, the adoption of a green production strategy provides a route‐map for enterprises to enhance their green dynamic capability (Kjaerheim, 2005).…”
Section: Introductionmentioning
confidence: 99%